1999
DOI: 10.1046/j.1442-2018.1999.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the grounded theory approach to a novice researcher

Abstract: The grounded theory approach has been used in nursing research since 1970. The latest methodological books describe the research process in detail. However, there are many problems involved in the grounded theory approach, which especially need to be considered by a novice researcher. One of these problems is the question of how deeply and widely the researcher should familiarize her- or himself with the research topic before the empirical study. The problems also include the need to focus the research problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 30 publications
0
98
0
11
Order By: Relevance
“…Any new categorisations were then tested against articles read earlier. Throughout the analyses, key elements of the constant comparison process, such as the production of memos to record initial thoughts concerning our 'dialogue with the data' (Backman and Kyngäs 1999), were acknowledged. Following the completion of this process, categorical saturation (Brod et al 2009) was confirmed by an analysis of those articles not included in the first tranche.…”
Section: A Tentative But Concise Characterisation Of Foundational Nummentioning
confidence: 99%
“…Any new categorisations were then tested against articles read earlier. Throughout the analyses, key elements of the constant comparison process, such as the production of memos to record initial thoughts concerning our 'dialogue with the data' (Backman and Kyngäs 1999), were acknowledged. Following the completion of this process, categorical saturation (Brod et al 2009) was confirmed by an analysis of those articles not included in the first tranche.…”
Section: A Tentative But Concise Characterisation Of Foundational Nummentioning
confidence: 99%
“…6,32 The literature can be used to identify that a new approach is needed to solve an old problem even though it has been well studied in the past. 6,19,46 Marland 6 found this to be true when he was able to develop a theory free of the methodological and conceptual pitfalls of previous studies whilst also bridging perceived gaps in existing knowledge. He argued that his preliminary review of the literature was vital to demonstrate his proposed approach had not been taken before and therefore the result would constitute a unique addition to knowledge.…”
Section: To Meet Committee Requirements and Assist With Methodologicamentioning
confidence: 99%
“…This approach can help to provide a detailed picture on a topic and may uncover surprising findings that have previously been missed. However, it is time-and labour-intensive, requiring substantial knowledge of the techniques involved in undertaking and analysing data, which may be confusing to researchers unfamiliar with grounded theory (Backman & Kyngäs, 1999 …”
Section: Grounded Theory Approachmentioning
confidence: 99%
“…Like case studies, grounded theory is an approach to guide research design, rather than a method (Backman & Kyngäs, 1999). Researchers can use a variety of data collection methods such as in-depth, qualitative interviews, participant observation or document analysis.…”
Section: Grounded Theory Approachmentioning
confidence: 99%